Theory and modeling of dispersed multiphase turbulent reacting flows - Zhou, Lixing (Butterworth-Heinemann, 2018)
Theory and Modeling of Dispersed Multiphase Turbulent Reacting Flows gives a systematic account of the fundamentals of multiphase flows, turbulent flows and combustion theory. It presents the latest advances of models and theories in the field of dispersed multiphase turbulent reacting flow, covering basic equations of multiphase turbulent reacting flows, modeling of turbulent flows, modeling of multiphase turbulent flows, modeling of turbulent combusting flows, and numerical methods for simulation of multiphase turbulent reacting flows, etc. The book is ideal for graduated students, researchers and engineers in many disciplines in power and mechanical engineering.